Paddy farmers in Kerala are willing to pay more for a modified crop insurance product - Anirudh K C; Aditya K S; Subash Surendran Padmaja; Anil Kuruvila (Agricultural Economics Research Review, 2023)
We study paddy farmers in Kerala and analyse the factors affecting their willingness to pay for crop insurance and for a hypothetical crop insurance product. The farmers are willing to pay higher premium rates if claims are settled based on the procurement price, instead of cultivation cost, and promptly; and individual losses are accounted for. A farmer’s willingness to pay more is influenced positively by their landholding size and negatively by age. Infrastructural support, and efficient implementation, will help to resolve the design-–reality gaps in insurance schemes. Designing popular schemes will reduce the subsidy burden on the public exchequer.